Racial difference in mortality among COVID-19 hospitalizations in California - Muni Rubens; Venkataraghavan Ramamoorthy; Anshul Saxena; Juan Carlos Zevallos; Juan Gabriel Ruiz Pelaez; Md Ashfaq Ahmed; Zhenwei Zhang; Peter McGranaghan; Sandra Chaparro; Javier Jimenez (Scientific Reports, 2023)
Abstract In the US, racial disparities in hospital outcomes are well documented. We explored whether race was associated with all-cause in-hospital mortality and intensive care unit (ICU) admission among COVID-19 patients in California. This was a retrospective analysis of California State Inpatient Database during 2020. Hospitalizations ≥ 18 years of age for COVID-19 were included. Cox proportional hazards with mixed effects were used for associations between race and in-hospital mortality. Logistic regression was used for the association between race and ICU admission. Among 87,934 COVID-19 hospitalizations, majority were Hispanics (56.5%), followed by White (27.3%), Asian, Pacific Islander, Native American (9.9%), and Black (6.3%). Cox regression showed higher mortality risk among Hispanics, compared to Whites (hazard ratio, 0.91; 95% CI 0.87–0.96), Blacks (hazard ratio, 0.87; 95% CI 0.79–0.94), and Asian, Pacific Islander, Native American (hazard ratio, 0.89; 95% CI 0.83–0.95). Logistic regression showed that the odds of ICU admission were significantly higher among Hispanics, compared to Whites (OR, 1.70; 95% CI 1.67–1.74), Blacks (OR, 1.70; 95% CI 1.64–1.78), and Asian, Pacific Islander, Native American (OR, 1.82; 95% CI 1.76–1.89). We found significant disparities in mortality among COVID-19 hospitalizations in California. Hispanics were the worst affected with the highest mortality and ICU admission rates.